Discovery of Novel Viruses in Culicoides Biting Midges in Chihuahua, Mexico - Laredo Tiscareño, S. Viridiana; Garza Hernandez, Javier Alfonso; Rodríguez-Alarcón, Carlos Arturo; Beristain-Ruiz, Diana Marcela; Rubio Tabarez, Ezequiel; S. Tangudu, Chandra; Dankaona, Wichan; Adame Gallegos, Jaime R.; De Luna Santillana, Erick J.; Huerta, Herón; Gonzalez Peña, Rodolfo; Rivera Martínez, Alejandra; et al. (2024)
Biting midges (Culicoides) are vectors of many pathogens of medical and veterinary importance, but their viromes are poorly characterized compared to certain other hematophagous arthropods, e.g., mosquitoes and ticks. The goal of this study was to use metagenomics to identify viruses in Culicoides from Mexico. A total of 457 adult midges were collected in Chihuahua, northern Mexico, in 2020 and 2021, and all were identified as female Culicoides reevesi. The midges were sorted into five pools and homogenized. An aliquot of each homogenate was subjected to polyethylene glycol precipitation to enrich for virions, then total RNA was extracted and analyzed by unbiased high-throughput sequencing. We identified six novel viruses that are characteristic of viruses from five families (Nodaviridae, Partitiviridae, Solemoviridae, Tombusviridae, and Totiviridae) and one novel virus that is too divergent from all classified viruses to be assigned to an established family. The newly discovered viruses are phylogenetically distinct from their closest known relatives, and their minimal infection rates in female C. reevesi range from 0.22 to 1.09. No previously known viruses were detected, presumably because viral metagenomics had never before been used to study Culicoides from the Western Hemisphere. To conclude, we discovered multiple novel viruses in C. reevesi from Mexico, expanding our knowledge of arthropod viral diversity and evolution.